2014
DOI: 10.1002/ijc.28730
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) genotypes in an Australian sample of anal cancers

Abstract: Human papillomavirus (HPV) causes most cases of anal cancers. In this study, we analyzed biopsy material from 112 patients with anal cancers in Australia for the presence of HPV DNA by the INNO LiPA HPV genotyping assay. There were 82% (92) males and 18% (20) females. The mean age at diagnosis was significantly (p 5 0.006) younger for males (52.5 years) than females (66 years). HIV-infected males were diagnosed at a much earlier mean age (48.2 years) than HIV negative (56.3 years) males (p 5 0.05). HPV DNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 23 publications
2
36
1
Order By: Relevance
“…Considering a large majority of anal cancers are caused by HPV16 (26), this suggests that the composite-AIN3 category more accurately represents true "anal precancer" than the composite AIN2 category, as is the case in the cervix (27). In a recent Australian study of 112 anal cancer samples analyzed for the presence of HPV DNA, 108 (96%) were HPV DNA positive and, of those, 81 (75%) were positive for HPV16 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Considering a large majority of anal cancers are caused by HPV16 (26), this suggests that the composite-AIN3 category more accurately represents true "anal precancer" than the composite AIN2 category, as is the case in the cervix (27). In a recent Australian study of 112 anal cancer samples analyzed for the presence of HPV DNA, 108 (96%) were HPV DNA positive and, of those, 81 (75%) were positive for HPV16 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Strengths include: (i) characterisation HPV genotypes using multivalent detection; (ii) a contemporaneous study of a UK clinical series that complements recent publications from Australia [5] and the wider world [31]; (iii) the novel exploration of HPV 16 E6 variants, as putative more aggressive oncogenic HPV subtypes; and (iv) a linkage of the laboratory findings to detailed clinical data to allow multivariate prognostic modelling.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…In 2009, a metaanalysis of 29 studies [3], using mainly historical detection assays, reported an estimate for HPV positivity of 84.3%. Recently published data suggest that the overall HPV positivity rate might be as high as 95% [4,5].…”
Section: Introductionmentioning
confidence: 97%
“…naive or long-term HAART users) and the unavailability of a measure of HPV DNA, particularly from the anus, that prevented us from distinguishing seropositivity related to past or present infections. Although we had L1 serological assays for only eight of the 12 HPV types that have been designated as high-risk based on their carcinogenicity at the cervix, and only HPV16-E6, HPV16 is the only HPV type established as a cause of anal cancer [34], and is by far the predominantly detected type in large cases series of anal cancer [2,35], including those diagnosed among HIV-positive persons [36,37]. In addition, there is evidence for some cross-reactivity of HPV E6, but not L1, assay antigens, for antibodies of closely phylogenetically related types [13].…”
Section: Pos At Haart Initiation Pos At 24-month Follow-up Prevalencementioning
confidence: 99%